Distribution of yeast species associated with oral lesions in HIV-infected patients in Southwest Uganda - Agwu, Ezera; Ihongbe, John C.; MCManus, Brenda A.; Moran, Gary P.; Coleman, David C.; Sullivan, Derek J. (Medical Mycology, 2012)
Oropharyngeal candidiasis remains a signifi cant clinical problem in HIV-infected and AIDS patients in regions of Africa where anti-retroviral therapy isn ’ t readily available. In this study we identifi ed the yeast populations associated with oral lesions in HIV-infected patients in Southwest Uganda who were receiving treatment with nystatin and topical clotrimazole. Samples were taken from 605 patients and 316 (52%) of these yielded yeast growth following incubation on Sabouraud dextrose agar. Samples were subsequently re-plated on CHROMagar Candida medium to facilitate identifi cation of the yeast species pr esent. The majority (56%) of culturepositivesamples yielded a mix of two or more species. Candida albicans was present in 87% (274/316) of patient samples and accounted for 87% (120/138) of single species samples. Candida glabrata , Candida tropicalis and Candida norvegensis were also found in cultures that yielded a single species. No Candida dubliniensis isolates were identifi ed in this population.
Keywords: prevalence; yeast species; Candida; HIV; oropharyngeal